LEADERSHIP IN MERGER AND ACQUISITION SITUATION: A CASE REVIEW OF LUFTHANSA SERVICE GmbH (LSG) and Sky Chefs Inc. - Lufina Mahadewi (Journal of Management and Business Review, 2012)
This article proposes a relation and linkage between leadership aspects and their involvement in managing the soft factor issues post-Merger and Acquisition (M&A) to achieve the best outcome. The relation and linkage is drawn from the analysis of M&A and leadership aspects. The analysis shows that leadership plays a significant role as a fundamental mechanism in successful change. The author proposes that leadership is one of the key success factors in overall M&A process. This view is supported by consideration of Lufthansa Service GmbH (LSG) and Sky Chefs Inc case study.